2001
DOI: 10.1159/000055357
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of Human Interleukin-17 Gene-Transfected Meth-A Fibrosarcoma Cells Induces T Cell-Dependent Tumor-Specific Immunity in Mice

Abstract: Objective: The biological activities of interleukin-17 (IL-17), a newly cloned cytokine, have not been fully elucidated. The present study was designed to assess the in vitro and in vivo effect of transfecting the IL-17 gene into tumor cells. Methods: A complementary DNA (cDNA) encoding human IL-17 (hIL-17) was obtained by polymerase chain reaction amplification from the human CD4+ T cell cDNA library and inserted into the plasmid pRc/cytomegalovirus to construct an expression vector for the hIL-17 gene. Murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 26 publications
0
80
0
1
Order By: Relevance
“…However, the role of IL-17 and Th17 cells in antitumor immunity remains controversial. In some tumor models, expression of IL-17 can boost antitumor immunity by promoting the development of Ag-specific cytotoxic T cells (47,48). Tumorspecific Th17 cells have been shown to eradicate established and advanced B16 melanoma in an adoptive transfer therapeutic tumor model (49).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of IL-17 and Th17 cells in antitumor immunity remains controversial. In some tumor models, expression of IL-17 can boost antitumor immunity by promoting the development of Ag-specific cytotoxic T cells (47,48). Tumorspecific Th17 cells have been shown to eradicate established and advanced B16 melanoma in an adoptive transfer therapeutic tumor model (49).…”
Section: Discussionmentioning
confidence: 99%
“…Forced overexpression of Il-17 ectopically in tumor cells can either suppress tumor progression through enhanced antitumor immunity (12,30) or promote it through an increase in inflammation and angiogenesis (11). the role of endogenous Il-17 in tumorigenesis has been assessed with Il-17 knockout mice (13).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the effect of IL-17 on in vivo tumor growth seems to depend largely on the tumor immunogenicity and cell types, as we and other groups have shown that IL-17 inhibits tumor growth in a T-cell-dependent manner. 24,46 In contrast, IL-17 has also been shown to promote tumor cell growth via proangiogenic and IL-6-dependent mechanisms. 12,35,47 In the present study, 5 out of 10 MF/SS biopsies expressed IL-17, but in this small series of patients, no clear-cut difference in the expression of this cytokine was observed in MF or SS patients.…”
Section: Discussionmentioning
confidence: 99%